2017
DOI: 10.1177/0963689717720282
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Microvasculature in PDMS Networks Using Endothelial Cells Derived from Human Induced Pluripotent Stem Cells

Abstract: In this study, we used a polydimethylsiloxane (PDMS)-based platform for the generation of intact, perfusion-competent microvascular networks in vitro. COMSOL Multiphysics, a finite-element analysis and simulation software package, was used to obtain simulated velocity, pressure, and shear stress profiles. Transgene-free human induced pluripotent stem cells (hiPSCs) were differentiated into partially arterialized endothelial cells (hiPSC-ECs) in 5 d under completely chemically defined conditions, using the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Multiple groups have demonstrated the possible therapeutic benefits of using stem cell-derived ECs for treating diseases, including hind limb ischemia, myocardial infarction, and long-term survival after graft implantation [37, 5052]. This study demonstrated that exposure to appropriate shear stress enhanced mouse iPSCs towards arterial ECs via Notch signaling pathways.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Multiple groups have demonstrated the possible therapeutic benefits of using stem cell-derived ECs for treating diseases, including hind limb ischemia, myocardial infarction, and long-term survival after graft implantation [37, 5052]. This study demonstrated that exposure to appropriate shear stress enhanced mouse iPSCs towards arterial ECs via Notch signaling pathways.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, distinct differences were observed in the Matrigel assay, including more tube numbers and longer tube length appearing to be fairly functionally mature cells with an arterial-like phenotype [22]. Additionally, cells could align parallel to the direction of flow, demonstrating flow-sensing ability similar to in vivo vessels [37]. Lastly, shear stress upregulated the amount of NO secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various advantages for application in biohybrid lung assist, PDMS is known to be hydrophobic and a surface material that naturally does not promote endothelial cell adhesion 17 . Other groups already succeeded in endothelial cell coating of PDMS surfaces of different geometries 29,30 . For proteins as a PDMS surface coating, there are disadvantages for long‐time application like proteolysis, denaturation, or conformational changes described 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The hMEVC endothelium-on-chip developed can be further improved and validated by confirmation of molecular markers such as VE-cadherin (vascular endothelial cadherin) and selective permeability, although we confirmed the confluency of endothelial cells using membrane staining. Incorporation of soft substrates such as PDMS 48 and collagen matrices 14 will provide hMVEC with more in vivo-like environment than rigid glass slide. Moreover, collagen matrices will also allow full observation of TEM of cancer cells.…”
Section: Discussionmentioning
confidence: 99%